Penerapan Metode Omnibus Law dalam Pembentukan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Fajar Kurniyasih; Ika Setyorini (Program Studi Ilmu Hukum Fakultas Syari'ah dan Hukum Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
The application of an Omnibus Law method first full-length time is used in Indonesia in the formation of the Law No. 11 Year 2020 about Cipta Kerja. This certainly need to examined will the adoption of an Omnibus Law method in the formation of the Law Cipta Kerja in accordance with the procedures and the principles for the formation of legislations in Indonesia. This study using qualitiative methodology through approach normative juridical that have been analyzed a sort of descriptive set with conducted research on the application of an Omnibus Law method in the of the Law Cipta Kerja and legislations which are related. In this context discusses how the law in the formation of an omnibus legislation, in Indonesia the application of an Omnibus Law method in the of the Law Cipta Kerja in the formation and the discourse.Through this research, the results obtained that the Omnibus Law Method has been substantively carried out in Indonesia in the formation of several laws and regulations and the position of Omnibus Law is as a method. An Omnibus Law has not been regulated in of Law No. 12 Year 2011 that has been converted in of Law No. 15 Year 2019 at about rule the formation of legislation, so there will be a different on a number of clauses in the preparation of the Law Cipta Kerja. This then creates a discourse in its application which has implications for the quality of The Law Cipta Kerja.